(untitled) (Journal of Computational Innovation and Analytics (JCIA), 2025)
This research examines sustainability in a social enterprise, delving into the quantitative variables, namely, social impact, social mission, and financial responsibility towards financial performance. This study evaluated whether businesses practicing social entrepreneurship were sufficiently sustainable in light of media accounts that report their economic and community performance. By examining key indicators across economic, community, and financial performance, this study provides evidence-based insights into their contributions to sustainable development and identifies areas for improvement. The participants are Metro Manila-based social enterprises that have been operating for over five years. The inclusion criteria for the social enterprises were the following: (1) sought a mission to solve social problems, (2) established a sustainable model, and (3) recognized by domestic opinion leaders to be innovative and potentially leading to more considerable systematic change. The quantitative data were analyzed using R Statistics Environment and Statistical Package for the Social Sciences (SPSS) version 23. The data was summarized in frequency tables, and the output was presented using descriptive statistics. The ratio and gathered data were tested using the Multiple Regression Analysis (MRA) to show the effect between dependent and independent variables. The results show that Economic Performance and Community Performance significantly influence most sustainability metrics of the study subjects. Among the sustainability variables, only social mission had a significant impact on Return on Assets and Return on Equity. Social enterprises may utilize the results from this study to formulate better ideas in their respective fields and create opportunities to make their businesses more sustainable.